Development of biobased coatings for controlled release fertilizers and phosphorus use efficiency by wheat - Cancellier, Eduardo Lopes (2017)
While controlled release nitrogen (N) fertilizers demonstrated to have agronomic and environmental advantages over their fully soluble alternatives, little is known about the effect of controlled release fertilizers (CRF) on phosphorus (P) use efficiency. In spite of these benefits, the use of petroleum-based non-biodegradable coatings is expensive and pollutes soil, rising the demand for new types of coating produced from inexpensive biobased materials. On new coatings research numerous samples need to be tested and methods to determine nutrient release rates from CRF usually rely on chemical analyses, which are timeconsuming and/or expensive. Therefore, the goals were to (i) develop an innovative and rapid low-cost method to evaluate nutrient release from CRF using conductometry; (ii) test biobased materials as coatings to produce CRF; and (iii) to investigated the potential of controlled release P fertilizers to reduce P fixation and increase P use efficiency. To achieve that, nutrient release in water was determined by measuring the electric conductivity (EC) over time, with intervals dependent on release rates. For soluble salt fertilizers, EC can be immediately determined and converted to concentration using a calibration curve. In the case of urea, an additional step is needed to convert the EC-neutral urea into ammonium. A validation test demonstrated strong agreement with the release determined using the EC method and analytical techniques. The new method hence offers an easy way to quickly evaluate over time the release of nutrients from CRF. For the coating development, a set of biobased materials was tested as coatings to produce CRF, consisting of combinations of wood resins with lignin and biobased sources of polyols for polyurethane synthesis. The biobased source of polyols demonstrated to be suitable for production of high performance CRF. It reduced MAP and urea release rates to 208 and 34 days respectively using as little as 6% of coating on MAP and 10% on urea. To assess the performance of these fertilizers, three CRF were prepared by coating MAP, with a release time of 7, 37 and 209 days. These fertilizers were incubated in soil for 70 days and chemical analyses of P in the soil and fertilizer were carried out. Also a pot trial with wheat was carried out to assess the agronomic effectiveness, using isotopic 33 P tracer. A lower release rate did not decrease P fixation in the calcareous soil, but had an effect in the Oxisol for the fertilizer with 37 days release. In the pot trial, the CRF either had no effect on yield or even decreased the yield in comparison with the control uncoated-MAP, particularly for the fertilizers with the slowest release rate. However, for MAP with 37 days for release, the P uptake was higher than for the control MAP in the Oxisol, indicating that controlled release does have potential to reduce fixation by oxides and hence increase P uptake. Although reduction in fixation was observed to a limited extend, the increase in P uptake was substantial (56%). It evidences that it is possible to improve P use efficiency by controlled release MAP.